Halal Industry Growth: Economic Opportunities And Challenges In Global Markets - Noviyanti, Ririn; Hakim, Rahmad (Program Studi Ekonomi Syariah, FEBI UIN Datokarama Palu, 2025)
The halal industry has emerged as a significant driver of global economic growth, extending beyond food and beverages to encompass sectors such as finance, tourism, cosmetics, and pharmaceuticals. Despite its rapid expansion, academic literature remains limited in assessing the industry's comprehensive macroeconomic contributions across diverse regions. This study aims to examine the economic impact and growth dynamics of the global halal industry by identifying its most prominent sectors and emerging market opportunities. Utilizing a Systematic Literature Review (SLR) guided by the PRISMA framework, the study synthesizes findings from peer-reviewed journals, industry reports, and institutional data published between 2014 and 2024. The analysis indicates that halal food and beverages remain the dominant contributors to economic output, while halal tourism, modest fashion, cosmetics, and pharmaceuticals exhibit substantial growth potential. The industry contributes significantly to GDP, employment generation, and foreign investment, particularly in countries such as Malaysia, Indonesia, and the United Arab Emirates. However, challenges persist, including regulatory fragmentation and limited technological integration. The findings highlight the need for harmonized global halal standards, enhanced investment in infrastructure, and the adoption of digital innovations to strengthen the industry's global competitiveness. This study advances the academic discourse by offering a comprehensive economic perspective on the halal industry and provides actionable insights for policymakers, industry stakeholders, and investors.